1976
DOI: 10.1073/pnas.73.12.4645
|View full text |Cite
|
Sign up to set email alerts
|

Human alpha-fetoprotein as a modulator of human lymphocyte transformation: correlation of biological potency with electrophoretic variants.

Abstract: Human alpha-fetoprotein (HAFP) isolated by immunoadsorbent column was shown to suppress the mitogenic response of human lymphocytes to phytomitogens, antihuman thymocyte antiserum, and the mixed lymphocyte culture. HAFP isolated from the sera and ascitic fluid of five hepatoma patients, and from fetal liver, varied in biological potency over three orders of magnitude. Extended agarose gel electrophoresis and crossed immunoelectrophoresis demonstrated three molecular species of HAFP. Quantitation of the three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…One possibility would be cross-reactivity with steroids or steroid receptors that would result in effects similar to those observed by Wright et al (1982) and Rider et al (1987) who used a monoclonal antiprogesterone antibody. Alpha fetoprotein is reported to have immunosuppressive activity (Lester et al, 1976;Murgita et al, 1976) and has a molecular weight of 68 000 similar to that of TsF under alkaline conditions (Figs 1 & 2). However, that the immunoreactive band is not alpha-fetoprotein is evident from the apparent molecular weight under acidic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility would be cross-reactivity with steroids or steroid receptors that would result in effects similar to those observed by Wright et al (1982) and Rider et al (1987) who used a monoclonal antiprogesterone antibody. Alpha fetoprotein is reported to have immunosuppressive activity (Lester et al, 1976;Murgita et al, 1976) and has a molecular weight of 68 000 similar to that of TsF under alkaline conditions (Figs 1 & 2). However, that the immunoreactive band is not alpha-fetoprotein is evident from the apparent molecular weight under acidic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…From each of these three sources, a-fetoprotein was isolated by passage over an anti-a-fetoprotein immunoadsorbent column. Trace impurities were removed by subsequent passage over an anti-whole human serum immunoadsorbent column and Sephadex G-150, as described (1,2). In addition, a-fetoprotein was isolated from a homogenate of fetal livers of 15-to 20-week-old stillborn human abortuses.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously characterized a-fetoprotein microheterogeneity by crossed immunoelectrophoresis in agarose gels and have demonstrated that there is variation of a charged moiety other than sialic acid on the molecule (1). Furthermore, the relative proportion of the most electronegative form of a-fetoprotein in an individual a-fetoprotein isolate correlates with its immunosuppressive potency (1). We now report on the microheterogeneity and immunosuppressive potency of a-fetoprotein isolated from the serum, ascitic fluid, and tumor of a single patient (Gd) dying of a malignant hepatoma.…”
mentioning
confidence: 99%
“…Some of the discrepancies may be due to the existence of microheterogeneous variants of AFP which differ in their biological properties [83].…”
Section: Afp and Immunoregulationmentioning
confidence: 99%